PENUMPASAN PGRS-PARAKU DI KECAMATAN SUNGAI RAYA KEPULAUAN KABUPATEN BENGKAYANG TAHUN 1963-1970 - Tika Audina; Agus Sastrawan Noor; Andang Firmansyah (Jurnal Pendidikan dan Pembelajaran Khatulistiwa (JPPK), 2019)
AbstractThe general research problem was the destruction process of PGRS-PARAKU in Sungai Raya Kepulauan, Bengkayang Regency in 1963-1970. The problems raised in this study were summarized in three research questions, the entry of PGRS-PARAKU in West Kalimantan, the background of the destruction of PGRS-PARAKU, and the conditions of PGRS-PARAKU after destruction in Sungai Raya Kepulauan, Bengkayang Regency in 1963-1970. To achieve the research purpose, researcher used historical research method. The techniques of data collection were interview and documentation. The result showed that the destruction of PGRS-PARAKU in Sungai Raya Kepulauan, Bengkayang Regency in 1963-1970 was motivated by the uprising of the volunteers who were gathered and trained by TNI in the border area of West Kalimantan because of the confrontation between Indonesia-Malaysia caused by the British that tried to gather their allies in Southeast Asia in a single unit, but that was challenged by Indonesian government. The researcher suggested that the society must begin to care about politics, pay attention to their surrounding and prioritize the logic so that the destruction of PGRS-PARAKU in Sungai Raya Kepulauan, Bengkayang Regency in 1963-1970 will not occurs anymore in the future. Keywords: Destruction, PGRS-PARAKU, West Kalimantan